S phase arrest in lymphocytes induced by urinary 1-hydroxypyrene and alcohol drinking in coke oven workers. (March 2018) - Yang, J; Zhang, H; Zhang, H; Pan, B; Wang, W; Fan, Y; Liu, Y
Arrest of the cell cycle after DNA damage is believed to promote DNA repair. We aim to investigate the main factors affecting cell cycle arrest of lymphocytes in coke oven workers. A total of 600 workers were included in this study, and their urinary levels of four polycyclic aromatic hydrocarbons (PAH) metabolites, 8-hydroxydeoxyguanosine (8-OHdG), and cell cycle distribution were determined. Urinary PAH metabolites were significantly increased in coke oven workers ( p < 0.01). It was found that only urinary 2-hydroxynaphthalene and 1-hydroxypyrene showed significant positive linear dose–response effects on 8-OHdG in this study population ( p trend = 0.025 and 0.017, respectively). The dose–response effect was also observed for smoking and drinking on 8-OHdG ( p trend < 0.001 and 0.034, respectively). Multivariate logistic regression analysis revealed that high levels of urinary 1-hydroxypyrene were associated with a significantly increased risk of S phase arrest (odds ratio (OR) = 1.32, p = 0.03), so as heavy alcohol drinking (OR = 1.31, p = 0.02). Drinking can significantly modify the effects of urinary 1-hydroxypyrene on S phase arrest, during co-exposure to both heavy drinking and median or high 1-hydroxypyrene levels (OR = 3.31, 95% confidence interval (CI) = 1.21–7.63 and OR = 2.56, 95% CI = 1.08–6.06, respectively). Our findings demonstrate that coke oven workers with heavy drinking will cause S phase arrest so as to repair more serious DNA damage.